Legal Protection of Concurrent Creditors for The Debts That are not Guaranteed by Property Rights According to Bankruptcy Law and Islamic Law - Risma Nur Arifah; Arman Safril Adam (Universitas Nurul Jadid, 2022)
Bankruptcy is a condition where the debtor is unable to fulfill his obligations to pay debts to creditors. Revision of Law Number 4 of 1998 became Law Number. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations explains that concurrent creditors are creditors who do not hold collateral and who do not have special rights and whose claims are not recognized or recognized conditionally, of course, this causes the position of concurrent creditors to be very vulnerable to getting their rights back on the debt of the bankrupt debtor. This research is normative research using a statutory approach and a conceptual approach, where in this study the researcher examined the regulations on bankruptcy through the Act and analyzes the concept of legal protection for concurrent creditors. The results of the study showed that, first, Law Number 37 of 2004 concerning Bankruptcy and PKPU (Postponement of Debt Payment Obligations) explains that concurrent creditors are conditional creditors and do not have special rights, their position in paying off debtors' debts from the remaining proceeds from the settlement or auction of bankrupt assets. Second, Islamic law stipulates that the guaranteed of legal protection for creditors is to fulfill debt obligations as regulated in Surah al Baqarah verse 282 based on the principle of al ‘adalah.